A new species of Mantispidae (Insecta: Neuroptera) from Central Amazonia, Brazil - Machado, Renato José Pires; Rafael, José Albertino (Zootaxa, 2007)
The genus Mantispa Illiger, now restricted to the Old World, was divided in six genera in the New World (Hoffman, 2002). Leptomantispa Hoffman, is one of them. This genus presently contains nine species occurring from southwestern Canada south to northern Argentina. Only one Brazilian species was listed by Hoffman (2002), L. chaos Hoffman. The Brazilian mantispids species studied by Penny (1982), Penny & Costa (1983) and Carvalho & Corseuil (1995), previously included in Mantispa, were examined. Some of them will be soon transferred to Leptomantispa. During this revision we found a new species described below.